Proportion of kindergarten children meeting the WHO guidelines on physical activity, sedentary behaviour and sleep and associations with adiposity in urban Beijing - Hongyan Guan; Zhiguang Zhang; Bo Wang; Anthony D. Okely; Meiling Tong; Jianxin Wu; Ting Zhang (BMC, 2020)
Abstract Background World Health Organisation (WHO) Guidelines on Physical Activity, Sedentary Behaviour and Sleep for Children under 5 Years of Age were released in 2019. The aim of this study was to examine the proportion of Chinese kindergarten children who met each individual guideline and each combination of the guidelines and the associations with adiposity. Methods Participants were 254 kindergarten children aged 4.1-6.3 years recruited from three kindergartens in urban area of Beijing. Physical activity, sedentary behaviour and sleep duration were assessed using 24-h accelerometry over three consecutive days. Screen time was reported by parents. Weight and height were measured; and children were categorised into normal weight and overweight/obese groups according to the WHO age- and sex- specific criteria. Frequency analyses were performed to examine the proportion of children meeting individual and combination of these guidelines. Logistics regression analyses were conducted to examine the associations between guideline compliance and adiposity. Results The proportion of children who met the physical activity (≥ 3 h daily physical activity, including ≥1 h daily moderate- to vigorous-intensity physical activity (MVPA)), sedentary screen time (< 1 h/day), and sleep guidelines (10-13 h/day) were 65.4, 88.2 and 29.5%, respectively; only 15.0% met all three guidelines and 2.7% did not meet any of the guidelines. Not meeting the physical activity guideline, sleep guideline, or combination of any two guidelines, or all three guidelines was not associated with overweight or obesity; however, children who did not meet the sedentary screen time guidelines were at higher risk for overweight and obesity (odds ratio = 3.76, 95% CI: 1.50-9.45). Conclusions In our study, only a small proportion of children met all three guidelines. Most Chinese kindergarten children met physical activity guidelines or screen time guidelines, whereas fewer children met sleep guideline. Not meeting sedentary screen time guidelines was associated with adiposity, which warrant further interventions for limiting screen time in young children.